Preparation method of high-strength conductive CuNiSi alloy

By adding Y elements and Co elements in the preparation process of CuNiSi alloy and using a specific melt cover agent, efficient smelting and production of CuNiSi alloys is achieved in the atmospheric environment, solving the problems of alloy composition control and quality stability, and achieving high-strength conductive CuNiSi alloys with excellent performance and suitable for industrial production.

CN119640089APending Publication Date: 2025-03-18FUZHOU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411702597.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively smel and produce high-strength conductive CuNiSi alloys with excellent performance in non-vacuum atmospheric environments, and CuNiSi alloys are prone to react with oxygen elements during the smelting process, resulting in difficult control of alloy components.

Method used

Smelting and casting in atmospheric environments is performed by adding Y and Co elements during the preparation of CuNiSi alloys and using specific melt covering agents, including acidified graphite and expanded perlite. The method includes multiple process steps such as batching, smelting and casting, homogenization treatment, hot rolling, solid solution treatment, cold rolling and aging treatment.

Benefits of technology

It realizes efficient production of high-strength conductive CuNiSi alloys with excellent performance in non-vacuum atmospheric environments, solving the problems of alloy composition control and quality stability, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640089A_ABST
    Figure CN119640089A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength conductive CuNiSi alloy. The copper alloy material comprises the following components in percentage by mass: 0.50 to 2.50 percent of Ni, 0.30 to 1.50 percent of Si, 0.50 to 2.50 percent of Co, 0.03 to 0.10 percent of Y and the balance of Cu. The preparation method comprises the following steps of burdening, non-vacuum melting and casting, homogenization treatment, hot rolling, solution treatment, primary cold rolling, regression treatment, secondary cold rolling and aging treatment. The components of the material do not contain toxic elements, a novel covering agent is adopted, the CuNiSi alloy can be produced in a large scale in a non-vacuum atmospheric environment, a novel combined thermomechanical treatment process is combined, the prepared CuNiSi alloy is excellent in comprehensive performance such as hardness, strength, plasticity and electric conductivity, and the service life of the CuNiSi alloy is prolonged. The composite material can be used for manufacturing electric connectors, conductive elastic sheets and other components required in the fields of aviation, spaceflight, new energy automobiles, electric power, electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy materials, and in particular relates to a method for preparing a high-strength conductive CuNiSi alloy. Background Art

[0002] High-strength conductive copper alloys are mainly used to prepare conductive elastic components, such as electrical connectors, conductive shrapnel, etc. They can be used in aviation, aerospace, new energy vehicles, electricity, electronics and other fields, and are important structural and functional integrated materials. This type of material mainly includes copper alloys such as CuBe, CuNiSn, CuTi, CuNiMn, CuNiAl, and CuNiSi. CuBe alloy has high strength, moderate conductivity, good wear resistance and impact spark-free properties, but its high-temperature stress relaxation resistance is poor, and it is not suitable for working at high temperatures for a long time. In addition, beryllium oxides and dust are highly carcinogenic, which will cause serious harm to the human body and the environment. CuNiSn alloy has high material strength and excellent wear resistance, but because the tin element is prone to reverse segregation and dendrite segregation during its melting and casting process, it is difficult to manufacture. CuTi alloy has good wear resistance and high strength, but its conductivity is low and its application range is limited. CuNiMn alloy has good performance in corrosion resistance and mechanical properties, but the Mn element evaporates severely during smelting, and it is not easy to accurately control the alloy composition. CuNiAl alloy has high strength, excellent high temperature thermal stability and corrosion resistance, but its electrical conductivity is low after deformation heat treatment.

[0003] CuNiSi alloy has the advantages of high strength, excellent bending resistance, high electrical conductivity, good stress relaxation resistance, good processing performance, and no sparks when impacted. It is a high-strength conductive copper alloy with a wide range of applications. However, Ni and Si elements are easily burned by reacting with oxygen elements during the smelting process, which makes the alloy composition difficult to control. At the same time, oxide inclusions will be formed to affect the quality of the ingot. Generally, it is necessary to melt and cast in a vacuum environment, which cannot meet the needs of large-scale industrial production. In the patents currently published, no research on the smelting of CuNiSi alloy in a non-vacuum atmosphere was found. In addition, the Chinese patent "Coating agent for smelting scrap brass and its application" (patent application number: 201410179707.3) and the Chinese patent "Coating agent for smelting copper alloy tubes" (patent application number: 201510063188.9) have made corresponding studies on covering agents used in the smelting of other types of copper alloys, but did not point out whether these covering agents can effectively protect the CuNiSi alloy melt in a non-vacuum atmosphere.

[0004] Therefore, through the collaborative innovation of melt covering agent, material composition and preparation process, a high-strength conductive CuNiSi alloy that can be melt-cast in a non-vacuum atmospheric environment with excellent performance and suitable for large-scale industrial production is prepared, which has important practical significance. Summary of the invention

[0005] The object of the present invention is to provide a high-strength conductive CuNiSi alloy which can be melt-casted in a non-vacuum atmospheric environment and has excellent performance and is suitable for large-scale industrial production, and a preparation method thereof.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The invention provides a high-strength conductive CuNiSi alloy, which comprises the following components by weight percentage: Ni: 0.50-2.50%, Si: 0.30-1.50%, Co: 0.50-2.50%, Y: 0.03-0.10%, and the balance is Cu. Ni, Si, Co and Y are added in the form of CuNi, CuSi, CuCo and CuY intermediate alloys.

[0008] The raw materials are respectively a Cu metal block with a purity of ≥99.9wt.%, a CuNi master alloy with a Ni content of ≤5wt.%, a CuSi master alloy with a Si content of ≤3wt.%, a CuCo master alloy with a Co content of ≤5wt.%, and a CuY master alloy with a Y content of ≤85wt.%.

[0009] The present invention also provides a method for preparing the high-strength conductive CuNiSi alloy, which comprises the following steps:

[0010] (1) Ingredients: by weight percentage: Ni: 0.50-2.50%, Si: 0.30-1.50%, Co: 0.50-2.50%, Y: 0.03-0.10%, and the rest is Cu, and Ni, Si, Co, and Y are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0011] Preferably, the raw materials are respectively a Cu metal block with a purity of ≥99.9wt.%, a CuNi master alloy with a Ni content of ≤5wt.%, a CuSi master alloy with a Si content of ≤3wt.%, a CuCo master alloy with a Co content of ≤5wt.%, and a CuY master alloy with a Y content of ≤85wt.%.

[0012] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add covering agent 1, raise the temperature to 1150-1250°C until the pure copper block is completely melted, and keep it warm for 3-6 minutes. Then add CuNi, CuSi, CuCo, and CuY intermediate alloy blocks, and then add covering agent 2, raise the temperature to 1250-1350°C, keep it warm for 10-20 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0013] Wherein, the covering agent 1 comprises the following components in weight percentage: 80-85wt.% of acidified graphite, 15-20wt.% of expanded perlite;

[0014] The preparation method of the covering agent one is: putting acidified graphite and expanded perlite into an oven respectively, drying at a temperature of 100-200°C for 20-30 minutes, then crushing them into particles with a particle size of 1-4 mm respectively, and finally mixing them according to the ratio of the covering agent one and stirring them evenly.

[0015] The second covering agent comprises the following components in weight percentage: 60-70wt.% of acidified graphite, 8-12wt.% of expanded perlite, 2-3wt.% of sodium carbonate, 3-4wt.% of calcium carbonate, 4-12wt.% of sodium fluoride, and 4-15wt.% of magnesium fluoride;

[0016] The preparation method of the second covering agent is as follows: acidified graphite, expanded perlite, sodium carbonate, calcium carbonate, sodium fluoride and magnesium fluoride are respectively put into an oven, the drying temperature is 100-200°C, the insulation time is 20-30 minutes, and then they are respectively crushed into particles with a particle size of 1-4 mm, and finally mixed according to the ratio of the second covering agent and stirred evenly.

[0017] (3) homogenization treatment: under the protection of pure argon, the alloy ingot obtained in step (2) is placed in a heat treatment furnace for homogenization treatment at a temperature of 900 to 950° C. for 1 to 2 hours, and then cooled to room temperature with the furnace;

[0018] (4) Hot rolling: The alloy ingot after homogenization is heated to 870-950°C and then hot rolled. The total deformation of the hot rolling is 60-80%, and the final rolling temperature is 700-800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0019] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 850 to 950°C for 1 to 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0020] (6) Primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 75-90%;

[0021] (7) regression treatment: under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment, the regression temperature is 900-950°C, the holding time is 0.5-3 minutes, and then it is quickly cooled to room temperature;

[0022] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 20 to 40%;

[0023] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 420-480° C. for 2-4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] (1) The present invention adds Y and Co elements to the CuNiSi ternary alloy. The role of the Y element is that, on the one hand, due to the relatively low Gibbs free energy of the reaction between Y and O, N, and H, the O, N, and H elements in the melt can be effectively removed, thereby purifying the melt and reducing the burning loss of the Ni, Si, Co, and Cu elements. Since the Si element dissolved in the Cu matrix will cause the electrical conductivity of the Cu alloy to drop seriously, and the mixing enthalpy between Si-Y is greater than the mixing enthalpy between Ni-Si and Co-Si, a Si-Y precipitation phase can be formed during aging, effectively reducing the solid solubility of the Si element in the Cu matrix. At the same time, the formation of the Si-Y precipitation phase can also play a role in precipitation strengthening, and the electrical conductivity and strength of the alloy can be improved at the same time. The role of the Co element is that Co can promote the precipitation of Ni and Si solute atoms from the Cu matrix. The Co atom and the Ni atom are in a competitive relationship. While promoting the formation of the Ni2Si phase, the Co atom and the Ni and Si atoms will also form a fine and dispersed (Ni, Co)2Si phase together, thereby significantly improving the effect of precipitation strengthening and improving the strength of the alloy. When Y is added to the alloy, Ni and Co can also form precipitation phases with Y, further improving the strength and conductivity of the alloy. By adding Ni, Co, Si, and Y in combination, various precipitation phases such as Co-Si, Ni-Si, Si-Y, Co-Y, and Ni-Y can be formed in the copper alloy, which has a composite dispersion strengthening effect and helps to improve the strength of the alloy.

[0026] (2) The covering agent used in the present invention during smelting has the characteristics of preventing melt oxidation and alloy element evaporation, keeping the melt warm, facilitating the absorption of inclusions and facilitating slag removal and separation. The functions of the components are as follows: the acidified graphite will expand rapidly after being heated in a non-vacuum environment, and cooperate with the expanded perlite to cover the melt relatively quickly, playing the role of heat preservation, air isolation and preventing the evaporation of alloy elements, and the expanded graphite flakes and perlite have the advantage of porous adsorption, which can absorb inclusions in the melt and play the role of purifying the melt; sodium carbonate and calcium carbonate can reduce the viscosity of the melt and slag on the one hand, and can form low-melting-point composite salts with oxides in the melt on the other hand, playing the role of removing impurities; sodium fluoride and magnesium fluoride as fluoride salts can improve the fluidity of the melt on the one hand, and can effectively remove harmful elements such as H, P, S in the melt on the other hand, and further purify the melt.

[0027] (3) The present invention adopts a process of hot rolling + solution treatment + primary cold rolling + regression treatment + secondary cold rolling + aging treatment for the alloy. By matching and regulating the corresponding process parameters of each processing step, the microstructure of the alloy, such as grain size, dislocation density and distribution, size and distribution of precipitated phases, etc., can be effectively improved, thereby improving the mechanical properties and electrical conductivity of the alloy.

[0028] (4) The copper alloy material of the present invention has excellent comprehensive mechanical properties and electrical conductivity, with a hardness of 235-280 HV, a yield strength of ≥680 MPa, a tensile strength of 720-880 MPa, an elongation after fracture of 5-15%, and an electrical conductivity of 40-45% IACS.

[0029] (5) The material composition of the present invention does not contain toxic elements. By adopting a new type of covering agent, CuNiSi alloy can be mass-produced in a non-vacuum atmospheric environment. Combined with a new combined deformation heat treatment process, the prepared CuNiSi alloy has excellent comprehensive properties such as hardness, strength, plasticity and conductivity, and can be used to manufacture electrical connectors, conductive springs and other components required in the fields of aviation, aerospace, new energy vehicles, electric power, and electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the metallographic structure diagram of the copper alloy material obtained in Example 1;

[0031] Figure 2 This is a transmission electron microscope image of the copper alloy material obtained in Example 1;

[0032] Figure 3 This is a photo of the internal defects of the copper alloy ingot obtained in Comparative Example 1;

[0033] Figure 4 This is the metallographic structure diagram of the copper alloy material obtained in Comparative Example 1;

[0034] Figure 5 This is a transmission electron microscope image of the copper alloy material obtained in Comparative Example 1; DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the embodiments, but it is not intended to limit the present invention. The main test methods and standards related to the present invention are as follows: the hardness of the copper alloy material is measured according to GB / T4340.1-2009 "Vickers hardness test for metal materials Part 1: Test method"; the yield strength, tensile strength and elongation of the copper alloy material are measured according to GB / T34505-2017 "Room temperature tensile test method for copper and copper alloy materials"; the conductivity of the copper alloy material is measured according to GB / T351-2019 "Method for measuring the resistivity of metal materials", and its value is compared with the international annealed copper standard (100% IACS, International Annealed Copper Standard).

[0036] The raw materials used in the following embodiments and comparative examples, such as pure copper block, CuNi, CuSi, CuCo and CuY, are respectively: a Cu metal block with a purity of ≥99.9wt.%, a CuNi master alloy with a Ni content of ≤5wt.%, a CuSi master alloy with a Si content of ≤3wt.%, a CuCo master alloy with a Co content of ≤5wt.%, and a CuY master alloy with a Y content of ≤85wt.%.

[0037] The covering agent 1 and / or covering agent 2 used in each embodiment and comparative example are prepared by similar methods, and the specific preparation methods are as follows:

[0038] The preparation method of the covering agent one is as follows: the raw materials for preparing the covering agent one (such as acidified graphite and / or expanded perlite) are placed in an oven respectively, the drying temperature is 100-200° C., the insulation time is 20-30 minutes, and then they are crushed into particles with a particle size of 1-4 mm respectively, and finally they are mixed according to the ratio of each raw material in the covering agent one and stirred evenly.

[0039] The preparation method of the covering agent 2 is as follows: the raw materials for preparing the covering agent 2 (such as acidified graphite, expanded perlite, sodium carbonate, calcium carbonate, sodium fluoride, and magnesium fluoride) are respectively put into an oven, the drying temperature is 100-200° C., the insulation time is 20-30 minutes, and then they are respectively crushed into particles with a particle size of 1-4 mm, and finally the raw materials in the covering agent 2 are mixed according to the ratio and stirred evenly.

[0040] Example 1

[0041] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 0.50wt.% Ni, 0.30wt.% Si, 0.50wt.% Co, 0.03wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0042] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (81wt.% of acidified graphite, 19wt.% of expanded perlite), raise the temperature to 1170°C until the pure copper block is completely melted, and keep it warm for 4 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (61wt.% of acidified graphite, 11wt.% of expanded perlite, 2wt.% of sodium carbonate, 3wt.% of calcium carbonate, 11wt.% of sodium fluoride, 12wt.% of magnesium fluoride), raise the temperature to 1300°C, keep it warm for 15 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0043] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 920°C for 1 hour, and then cooled to room temperature with the furnace;

[0044] (4) Hot rolling: The homogenized alloy ingot is heated to 870°C and then hot rolled. The total deformation of the hot rolling is 60% and the final rolling temperature is 750°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0045] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 850°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0046] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 75%;

[0047] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 900°C for a holding time of 2.5 minutes, followed by rapid cooling to room temperature;

[0048] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 20%;

[0049] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 420° C. for 4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0050] After testing, the obtained copper alloy material has a hardness of 246 HV, a yield strength of 699 MPa, a tensile strength of 733 MPa, an elongation after fracture of 11%, and a conductivity of 44% IACS. Figure 1 This is a metallographic structure photograph of the final product of Example 1, the grains are relatively small, and the grain size distribution is 5 to 30 μm. Figure 2 This is the transmission electron microscope photograph of Example 1, where small and uniform elliptical or circular precipitates can be observed, which are dispersed in the copper matrix and have a size distribution of 3 to 10 nm.

[0051] Example 2

[0052] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0053] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0054] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0055] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0056] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0057] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0058] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0059] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0060] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0061] After testing, the obtained copper alloy material has a hardness of 271 HV, a yield strength of 781 MPa, a tensile strength of 822 MPa, an elongation after fracture of 7%, and a conductivity of 41% IACS.

[0062] Example 3

[0063] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.50wt.%, Si: 0.90wt.%, Co: 1.50wt.%, Y: 0.10wt.%, and the remainder is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0064] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (85wt.% of acidified graphite, 15wt.% of expanded perlite), raise the temperature to 1200°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (64wt.% of acidified graphite, 12wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 12wt.% of sodium fluoride, 5wt.% of magnesium fluoride), raise the temperature to 1300°C, keep it warm for 10 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0065] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0066] (4) Hot rolling: The homogenized alloy ingot is heated to 900°C and then hot rolled. The total deformation of the hot rolling is 65% and the final rolling temperature is 720°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0067] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 850°C for 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0068] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 80%;

[0069] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 910°C for a holding time of 1 minute, followed by rapid cooling to room temperature;

[0070] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 25%;

[0071] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 460° C. for 2 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0072] After testing, the obtained copper alloy material has a hardness of 240 HV, a yield strength of 689 MPa, a tensile strength of 721 MPa, an elongation after fracture of 12%, and a conductivity of 45% IACS.

[0073] Example 4

[0074] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 2.00wt.%, Si: 1.20wt.%, Co: 1.00wt.%, Y: 0.06wt.%, and the remainder is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0075] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (83% acidified graphite, 17% expanded perlite), raise the temperature to 1190°C until the pure copper block is completely melted, and keep it warm for 4 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (64wt.% acidified graphite, 10wt.% expanded perlite, 3wt.% sodium carbonate, 3wt.% calcium carbonate, 8wt.% sodium fluoride, 12wt.% magnesium fluoride), raise the temperature to 1340°C, keep it warm for 17 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0076] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 950°C for 1 hour, and then cooled to room temperature with the furnace;

[0077] (4) Hot rolling: The alloy ingot after homogenization is heated to 890°C and then hot rolled. The total deformation of the hot rolling is 80% and the final rolling temperature is 780°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0078] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 920°C for 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0079] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 90%;

[0080] (7) regression treatment: under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 940°C for a holding time of 0.5 min, followed by rapid cooling to room temperature;

[0081] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 40%;

[0082] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 480° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0083] After testing, the obtained copper alloy material has a hardness of 268 HV, a yield strength of 759 MPa, a tensile strength of 811 MPa, an elongation after fracture of 8%, and a conductivity of 42% IACS.

[0084] Example 5

[0085] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 2.50wt.% Ni, 1.50wt.% Si, 2.00wt.% Co, 0.04wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0086] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (84wt.% of acidified graphite, 16wt.% of expanded perlite), raise the temperature to 1230°C until the pure copper block is completely melted, and keep warm for 3 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (70wt.% of acidified graphite, 8wt.% of expanded perlite, 2wt.% of sodium carbonate, 3wt.% of calcium carbonate, 6wt.% of sodium fluoride, 11wt.% of magnesium fluoride), raise the temperature to 1320°C, keep warm for 20 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool to room temperature to obtain an alloy ingot;

[0087] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 950°C for 2 hours, and then cooled to room temperature with the furnace;

[0088] (4) Hot rolling: The homogenized alloy ingot is heated to 930°C and then hot rolled. The total deformation of the hot rolling is 75% and the final rolling temperature is 760°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0089] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 950°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0090] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 80%;

[0091] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 950°C for a holding time of 2.5 minutes, followed by rapid cooling to room temperature;

[0092] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 20%;

[0093] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 480° C. for 4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0094] After testing, the obtained copper alloy material has a hardness of 275 HV, a yield strength of 805 MPa, a tensile strength of 860 MPa, an elongation after fracture of 6%, and a conductivity of 40% IACS.

[0095] Example 6

[0096] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 0.50wt.% Ni, 0.30wt.% Si, 1.00wt.% Co, 0.05wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0097] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (80wt.% of acidified graphite, 20wt.% of expanded perlite), raise the temperature to 1250°C until the pure copper block is completely melted, and keep warm for 5 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (60wt.% of acidified graphite, 12wt.% of expanded perlite, 2wt.% of sodium carbonate, 4wt.% of calcium carbonate, 11wt.% of sodium fluoride, and 11wt.% of magnesium fluoride), raise the temperature to 1350°C, keep warm for 20 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0098] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 930°C for 1 hour, and then cooled to room temperature with the furnace;

[0099] (4) Hot rolling: The homogenized alloy ingot is heated to 880°C and then hot rolled. The total deformation of the hot rolling is 60% and the final rolling temperature is 750°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0100] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 850°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0101] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 75%;

[0102] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 930°C for a holding time of 3 minutes, followed by rapid cooling to room temperature;

[0103] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0104] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 440° C. for 2 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0105] After testing, the obtained copper alloy material has a hardness of 247 HV, a yield strength of 720 MPa, a tensile strength of 738 MPa, an elongation after fracture of 12%, and a conductivity of 44% IACS.

[0106] Example 7

[0107] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 1.50wt.%, Y: 0.10wt.%, and the remainder is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0108] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (81wt.% of acidified graphite, 19wt.% of expanded perlite), raise the temperature to 1210°C until the pure copper block is completely melted, and keep warm for 5 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (69wt.% of acidified graphite, 9wt.% of expanded perlite, 3wt.% of sodium carbonate, 3wt.% of calcium carbonate, 5wt.% of sodium fluoride, 11wt.% of magnesium fluoride), raise the temperature to 1350°C, keep warm for 10 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0109] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 920°C for 2 hours, and then cooled to room temperature with the furnace;

[0110] (4) Hot rolling: The homogenized alloy ingot is heated to 920°C and then hot rolled. The total deformation of the hot rolling is 80% and the final rolling temperature is 740°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0111] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 870°C for 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0112] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 80%;

[0113] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 940°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0114] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 20%;

[0115] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 460° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0116] After testing, the obtained copper alloy material has a hardness of 252 HV, a yield strength of 771 MPa, a tensile strength of 784 MPa, an elongation after fracture of 12%, and a conductivity of 43% IACS.

[0117] Example 8

[0118] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.50wt.%, Si: 0.90wt.%, Co: 0.50wt.%, Y: 0.03wt.%, and the remainder is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0119] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (84wt.% of acidified graphite, 16wt.% of expanded perlite), raise the temperature to 1180°C until the pure copper block is completely melted, and keep it warm for 4 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (62wt.% of acidified graphite, 11wt.% of expanded perlite, 2wt.% of sodium carbonate, 4wt.% of calcium carbonate, 7wt.% of sodium fluoride, 14wt.% of magnesium fluoride), raise the temperature to 1310°C, keep it warm for 12 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0120] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 1 hour, and then cooled to room temperature with the furnace;

[0121] (4) Hot rolling: The homogenized alloy ingot is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 75% and the final rolling temperature is 730°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0122] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 880°C for 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0123] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 90%;

[0124] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 900°C for a holding time of 2.5 minutes, followed by rapid cooling to room temperature;

[0125] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 30%;

[0126] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 2 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0127] After testing, the obtained copper alloy material has a hardness of 255 HV, a yield strength of 780 MPa, a tensile strength of 795 MPa, an elongation after fracture of 11%, and a conductivity of 44% IACS.

[0128] Example 9

[0129] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 2.00 wt.% Ni, 1.20 wt.% Si, 2.50 wt.% Co, 0.05 wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0130] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (85wt.% of acidified graphite, 15wt.% of expanded perlite), raise the temperature to 1240°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (66wt.% of acidified graphite, 9wt.% of expanded perlite, 3wt.% of sodium carbonate, 3wt.% of calcium carbonate, 10wt.% of sodium fluoride, 9wt.% of magnesium fluoride), raise the temperature to 1280°C, keep it warm for 14 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0131] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 950°C for 2 hours, and then cooled to room temperature with the furnace;

[0132] (4) Hot rolling: The alloy ingot after homogenization is heated to 950°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 770°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0133] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 930°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0134] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 75%;

[0135] (7) regression treatment: under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment, the regression temperature is 950°C, the holding time is 0.75 minutes, and then it is rapidly cooled to room temperature;

[0136] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 40%;

[0137] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 420° C. for 4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0138] After testing, the obtained copper alloy material has a hardness of 244 HV, a yield strength of 697 MPa, a tensile strength of 731 MPa, an elongation after fracture of 11%, and a conductivity of 42% IACS.

[0139] Example 10

[0140] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 2.50wt.% Ni, 1.50wt.% Si, 1.00wt.% Co, 0.06wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0141] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1220°C until the pure copper block is completely melted, and keep warm for 3 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 9wt.% of expanded perlite, 2wt.% of sodium carbonate, 4wt.% of calcium carbonate, 11wt.% of sodium fluoride, 9wt.% of magnesium fluoride), raise the temperature to 1270°C, keep warm for 10 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool to room temperature to obtain an alloy ingot;

[0142] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 910°C for 1 hour, and then cooled to room temperature with the furnace;

[0143] (4) Hot rolling: The homogenized alloy ingot is heated to 910°C and then hot rolled. The total deformation of the hot rolling is 60% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0144] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 880°C for 2 hours, and then the alloy strip is rapidly cooled to room temperature;

[0145] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 70%;

[0146] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0147] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 25%;

[0148] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 460° C. for 4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0149] After testing, the obtained copper alloy material has a hardness of 270 HV, a yield strength of 794 MPa, a tensile strength of 828 MPa, an elongation after fracture of 7%, and a conductivity of 43% IACS.

[0150] Comparative Example 1

[0151] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0152] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive away the air above the melt. First, put the pure copper block into the melting furnace, raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0153] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0154] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0155] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0156] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0157] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0158] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0159] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0160] After testing, the obtained copper alloy material has a hardness of 198 HV, a yield strength of 572 MPa, a tensile strength of 598 MPa, an elongation after fracture of 3%, and a conductivity of 35% IACS.

[0161] This proves that the mechanical properties of the copper alloy material produced will be significantly deteriorated if the coating agent 1 and coating agent 2 are missing when smelting electrolytic copper. There are a large number of defects inside the alloy ingot, such as Figure 3 shown. Figure 4 This is a metallographic structure photograph of the final product of Comparative Example 1. The grain size is uneven, and more large grains can be observed. The grain size distribution is 10 to 120 μm. Figure 5 This is a transmission electron microscope photograph of comparative example 1, from which it can be observed that the precipitated phase in the copper matrix is ​​oval or circular, the amount is very small, and the size distribution of the precipitated phase is 40 to 60 nm.

[0162] Comparative Example 2

[0163] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0164] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. Put a pure copper block into the melting furnace, and then add a covering agent 1 (100wt.% of acidified graphite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add a covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0165] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0166] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0167] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0168] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0169] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0170] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0171] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0172] After testing, the obtained copper alloy material has a hardness of 225 HV, a yield strength of 629 MPa, a tensile strength of 663 MPa, an elongation of 6%, and a conductivity of 39% IACS.

[0173] That is to say, it is proved that when the component of covering agent 1 is only acidified graphite, the mechanical properties of the copper alloy material obtained therefrom are reduced, and the electrical conductivity is also reduced to a certain extent.

[0174] Comparative Example 3

[0175] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0176] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. Put the pure copper block into the melting furnace, and then add the covering agent 1 (100wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0177] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0178] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0179] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0180] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0181] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0182] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0183] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0184] After testing, the obtained copper alloy material has a hardness of 218 HV, a yield strength of 613 MPa, a tensile strength of 644 MPa, an elongation of 4%, and a conductivity of 38% IACS.

[0185] That is to say, it is proved that when the component of covering agent 1 is only expanded perlite, the mechanical properties of the copper alloy material obtained therefrom are significantly reduced, while the plasticity of the material is reduced and the electrical conductivity is also reduced to a certain extent.

[0186] Comparative Example 4

[0187] (1) Ingredients: Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the rest is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0188] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, heat it to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add covering agent II (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), heat it to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0189] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0190] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0191] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0192] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0193] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0194] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0195] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0196] After testing, the obtained copper alloy material has a hardness of 211 HV, a yield strength of 605 MPa, a tensile strength of 633 MPa, an elongation after fracture of 5%, and a conductivity of 37% IACS.

[0197] This proves that when the covering agent is added in the absence of molten alloy elements, the mechanical properties of the prepared copper alloy material will be significantly deteriorated, and the electrical conductivity will also decrease to a certain extent.

[0198] Comparative Example 5

[0199] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0200] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. Put the pure copper block into the melting furnace, and then add covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add covering agent 2 (72wt.% of acidified graphite, 10wt.% of expanded perlite, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0201] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0202] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0203] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0204] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0205] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0206] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0207] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0208] After testing, the obtained copper alloy material has a hardness of 216 HV, a yield strength of 618 MPa, a tensile strength of 641 MPa, an elongation of 5%, and a conductivity of 37% IACS.

[0209] That is to say, it is proved that when the components of the second covering agent lack sodium carbonate and calcium carbonate, the mechanical properties of the copper alloy material obtained therefrom are significantly reduced, and the electrical conductivity of the alloy is also reduced.

[0210] Comparative Example 6

[0211] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0212] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. Put a pure copper block into the melting furnace, and then add covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add covering agent 2 (83wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0213] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0214] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0215] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0216] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0217] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0218] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0219] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0220] After testing, the obtained copper alloy material has a hardness of 210 HV, a yield strength of 604 MPa, a tensile strength of 630 MPa, an elongation of 5%, and a conductivity of 36% IACS.

[0221] That is to say, it is proved that when the components of the second covering agent lack sodium fluoride and magnesium fluoride, the mechanical properties of the copper alloy material obtained will be significantly deteriorated, and the electrical conductivity will also decrease to a certain extent.

[0222] Comparative Example 7

[0223] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0224] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add a covering agent (82wt.% of acidified graphite and 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep warm for 6 minutes. Then add CuNi, CuSi, CuCo and CuY intermediate alloy blocks, raise the temperature to 1250°C, keep warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool to room temperature to obtain an alloy ingot;

[0225] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0226] (4) Hot rolling: The homogenized alloy ingot is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0227] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0228] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0229] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0230] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0231] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0232] After testing, the obtained copper alloy material has a hardness of 204 HV, a yield strength of 576 MPa, a tensile strength of 590 MPa, an elongation after fracture of 4%, and a conductivity of 36% IACS.

[0233] This proves that when the coating agent 2 is added in the absence of molten alloy elements, the mechanical properties of the prepared copper alloy material will be significantly deteriorated, and the electrical conductivity will also decrease to a certain extent.

[0234] Comparative Example 8

[0235] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, and the remainder is Cu, wherein Ni, Si, and Co elements are added in the form of CuNi, CuSi, and CuCo master alloys;

[0236] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. Put a pure copper block into the melting furnace, and then add a covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add CuNi, CuSi and CuCo intermediate alloy blocks, and then add a covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0237] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0238] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0239] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0240] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0241] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0242] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0243] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0244] After testing, the obtained copper alloy material has a hardness of 209 HV, a yield strength of 598 MPa, a tensile strength of 604 MPa, an elongation after fracture of 8%, and a conductivity of 38% IACS.

[0245] This proves that when the Y element is not added, the mechanical properties of the prepared copper alloy material will significantly deteriorate, and the electrical conductivity will also decrease to a certain extent.

[0246] Comparative Example 9

[0247] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein Ni, Si, and Y elements are added in the form of CuNi, CuSi, and CuY master alloys;

[0248] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0249] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0250] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0251] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0252] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0253] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0254] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0255] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0256] After testing, the obtained copper alloy material has a hardness of 218 HV, a yield strength of 621 MPa, a tensile strength of 650 MPa, an elongation after fracture of 10%, and a conductivity of 41% IACS.

[0257] That is to say, it is proved that when the Co element is not added, the amount of precipitated phase of the prepared copper alloy material is reduced, resulting in a significant deterioration in the mechanical properties.

[0258] Comparative Example 10

[0259] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 5.00wt.%, Si: 3.00wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0260] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (85wt.% of acidified graphite, 15wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0261] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0262] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0263] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0264] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0265] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0266] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0267] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0268] After testing, the obtained copper alloy material has a hardness of 211 HV, a yield strength of 601 MPa, a tensile strength of 610 MPa, an elongation after fracture of 6%, and a conductivity of 34% IACS.

[0269] That is to say, when the Ni and Si elements exceed the range, the conductivity of the copper alloy material produced is significantly reduced and the mechanical properties are significantly deteriorated.

[0270] Comparative Example 11

[0271] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains 0.20wt.% Ni, 0.10wt.% Si, 2.50wt.% Co, 0.05wt.% Y, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0272] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0273] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0274] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0275] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0276] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0277] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0278] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0279] (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0280] After testing, the obtained copper alloy material has a hardness of 195 HV, a yield strength of 570 MPa, a tensile strength of 596 MPa, an elongation after fracture of 8%, and a conductivity of 44% IACS.

[0281] That is to say, when the Ni and Si elements are below the range, the mechanical properties of the prepared copper alloy material will deteriorate significantly.

[0282] Comparative Example 12

[0283] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0284] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0285] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0286] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0287] (5) Primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0288] (6) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0289] (7) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0290] (8) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0291] After testing, the obtained copper alloy material had a hardness of 186 HV, a yield strength of 560 MPa, a tensile strength of 571 MPa, an elongation after fracture of 6%, a conductivity of 38% IACS, and did not meet the size requirements.

[0292] This proves that when the solid solution treatment process is missing, the solute elements in the copper alloy cannot be fully absorbed by the Cu matrix, resulting in a significant deterioration in the mechanical properties of the material after aging, and a certain degree of decrease in the electrical conductivity.

[0293] Comparative Example 13

[0294] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0295] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0296] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0297] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0298] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0299] (6) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0300] (7) Cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0301] (8) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0302] After testing, the obtained copper alloy material has a hardness of 223 HV, a yield strength of 645 MPa, a tensile strength of 668 MPa, an elongation after fracture of 7%, and a conductivity of 40% IACS.

[0303] This proves that the mechanical properties of the copper alloy material produced will be reduced if a cold rolling process is missing between the solution treatment and the regression treatment.

[0304] Comparative Example 14

[0305] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0306] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0307] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0308] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0309] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0310] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0311] (7) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0312] (8) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0313] After testing, the obtained copper alloy material has a hardness of 216 HV, a yield strength of 615 MPa, a tensile strength of 639 MPa, an elongation after fracture of 6%, and a conductivity of 38% IACS.

[0314] This proves that without the regression treatment process, the mechanical properties of the prepared copper alloy material will be significantly deteriorated, and the electrical conductivity will also decrease to a certain extent.

[0315] Comparative Example 15

[0316] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0317] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0318] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0319] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0320] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0321] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0322] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0323] (8) Aging treatment: Under the protection of pure argon, the alloy strip after the regression treatment is placed in a heat treatment furnace for aging treatment at an aging temperature of 470° C. for 3 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

[0324] After testing, the obtained copper alloy material has a hardness of 225 HV, a yield strength of 656 MPa, a tensile strength of 668 MPa, an elongation after fracture of 13%, and a conductivity of 37% IACS.

[0325] That is to say, it is proved that the lack of a secondary cold rolling process between the regression treatment and the aging treatment will cause the mechanical properties of the prepared copper alloy material to deteriorate and the electrical conductivity to decrease to a certain extent.

[0326] Comparative Example 16

[0327] (1) Ingredients: Based on the sum of mass percentages being 100%, the alloy contains Ni: 1.00wt.%, Si: 0.60wt.%, Co: 2.50wt.%, Y: 0.05wt.%, and the remainder is Cu, wherein the Ni, Si, Co, and Y elements are added in the form of CuNi, CuSi, CuCo, and CuY master alloys;

[0328] (2) Melting and casting: Melting is carried out in an atmospheric environment, and a funnel-shaped gas protection cover is installed above the melting furnace. The protection cover can release pure argon gas above the melting furnace to drive out the air above the melt. First, put the pure copper block into the melting furnace, and then add the covering agent 1 (82wt.% of acidified graphite, 18wt.% of expanded perlite), raise the temperature to 1150°C until the pure copper block is completely melted, and keep it warm for 6 minutes. Then add the CuNi, CuSi, CuCo and CuY intermediate alloy blocks, and then add the covering agent 2 (65wt.% of acidified graphite, 10wt.% of expanded perlite, 3wt.% of sodium carbonate, 4wt.% of calcium carbonate, 8wt.% of sodium fluoride, 10wt.% of magnesium fluoride), raise the temperature to 1250°C, keep it warm for 18 minutes, then skim the alloy melt, and then cast the alloy melt into a mold and cool it to room temperature to obtain an alloy ingot;

[0329] (3) Homogenization treatment: Under the protection of pure argon, the alloy ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 2 hours, and then cooled to room temperature with the furnace;

[0330] (4) Hot rolling: The alloy ingot after homogenization is heated to 940°C and then hot rolled. The total deformation of the hot rolling is 70% and the final rolling temperature is 800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature.

[0331] (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 880°C for 1 hour, and then the alloy strip is rapidly cooled to room temperature;

[0332] (6) primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 85%;

[0333] (7) Regression treatment: Under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment at a regression temperature of 920°C for a holding time of 1.5 minutes, followed by rapid cooling to room temperature;

[0334] (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with a total cold rolling deformation of 35%;

[0335] After testing, the obtained copper alloy material has a hardness of 201 HV, a yield strength of 556 MPa, a tensile strength of 563 MPa, an elongation after fracture of 6%, and a conductivity of 25% IACS.

[0336] This proves that without the aging treatment process, the conductivity of the prepared copper alloy material will be significantly deteriorated, and the mechanical properties will also be greatly reduced.

[0337] The performance data of the above embodiments and comparative examples are shown in Table 1.

[0338] Table 1 Performance list of each embodiment and comparative example

[0339]

[0340]

[0341] The alloy ingots prepared in Comparative Example 2-16 also have internal defects, and the metallographic structure of the finished product also shows uneven grain size.

[0342] It can be seen from the above embodiments and comparative examples that the present invention can prepare a high-strength conductive CuNiSi alloy that can be melt-cast in a non-vacuum atmospheric environment and has excellent performance and is suitable for large-scale industrial production through collaborative innovation in three aspects: melt covering agent, material composition and preparation process, which has important practical significance.

Claims

1. A high-strength conductive CuNiSi alloy, characterized in that: Calculated by weight percentage, the present invention comprises the following components: Ni: 0.50-2.50%, Si: 0.30-1.50%, Co: 0.50-2.50%, Y: 0.03-0.10%, and the balance is Cu.

2. A method for preparing the high-strength conductive CuNiSi alloy as claimed in claim 1, characterized in that: It includes the following steps: (1) Ingredients: by weight percentage: Ni: 0.50-2.50%, Si: 0.30-1.50%, Co: 0.50-2.50%, Y: 0.03-0.10%, and the rest is Cu, wherein Ni, Si, Co, and Y are added in the form of CuNi, CuSi, CuCo, and CuY master alloys; (2) Melting and casting: Melting is carried out in an atmospheric environment. First, a pure copper block is placed in a melting furnace, and then a covering agent 1 is added. The temperature is raised to 1150-1250°C until the pure copper block is completely melted, and the temperature is kept warm for 3-6 minutes. Subsequently, CuNi, CuSi, CuCo, and CuY intermediate alloy blocks are added, and then a covering agent 2 is added. The temperature is raised to 1250-1350°C and the temperature is kept warm for 10-20 minutes. The alloy melt is then skimmed, and then the alloy melt is cast into a mold and cooled to room temperature to obtain an alloy ingot.

3. The method for preparing the high-strength conductive CuNiSi alloy according to claim 2, characterized in that: It consists of the following steps, performed in order: (3) homogenization treatment: under the protection of pure argon, the alloy ingot obtained in step (2) is placed in a heat treatment furnace for homogenization treatment at a temperature of 900 to 950° C. for 1 to 2 hours, and then cooled to room temperature with the furnace; (4) Hot rolling: The alloy ingot after homogenization is heated to 870-950°C and then hot rolled. The total deformation of the hot rolling is 60-80%, and the final rolling temperature is 700-800°C. The alloy strip after final rolling is immediately water quenched and rapidly cooled to room temperature. (5) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 850 to 950°C for 1 to 2 hours, and then the alloy strip is rapidly cooled to room temperature; (6) Primary cold rolling: removing the surface oxide scale of the alloy strip after solid solution treatment, and then cold rolling at room temperature, with a total cold rolling deformation of 75-90%; (7) regression treatment: under the protection of pure argon, the alloy strip after the primary cold rolling is placed in a heat treatment furnace for regression treatment, the regression temperature is 900-950°C, the holding time is 0.5-3 minutes, and then it is quickly cooled to room temperature; (8) Secondary cold rolling: removing the surface oxide scale of the alloy strip after regression treatment, and then performing secondary cold rolling at room temperature, with the total cold rolling deformation of 20-40%; (9) Aging treatment: Under the protection of pure argon, the alloy strip after secondary cold rolling is placed in a heat treatment furnace for aging treatment at an aging temperature of 420-480° C. for 2-4 hours, and then cooled to room temperature by air cooling to obtain the copper alloy strip.

4. The method for preparing a high-strength conductive CuNiSi alloy according to claim 2, characterized in that: In the step (2), a funnel-shaped gas protection cover is installed above the smelting furnace, and the protection cover can release pure argon gas above the smelting furnace to drive away the air above the melt.

5. The method for preparing the high-strength conductive CuNiSi alloy according to claim 2, characterized in that: The raw materials in step (2) are Cu metal blocks with a purity of ≥99.9wt.%, CuNi master alloys with a Ni content of ≤5wt.%, CuSi master alloys with a Si content of ≤3wt.%, CuCo master alloys with a Co content of ≤5wt.%, and CuY master alloys with a Y content of ≤85wt.%.

6. The method for preparing the high-strength conductive CuNiSi alloy according to claim 2, characterized in that: The covering agent 1 in step (2) comprises the following components by weight percentage: 80-85% of acidified graphite and 15-20% of expanded perlite.

7. The method for preparing the high-strength conductive CuNiSi alloy according to claim 6, characterized in that: The preparation method of the covering agent one is: putting acidified graphite and expanded perlite into an oven respectively, drying at a temperature of 100-200°C for 20-30 minutes, then crushing them into particles with a particle size of 1-4 mm respectively, and finally mixing them according to the ratio of the covering agent one and stirring them evenly.

8. The method for preparing a high-strength conductive CuNiSi alloy according to claim 2, characterized in that: The covering agent 2 in step (2) comprises the following components by weight percentage: 60-70% of acidified graphite, 8-12% of expanded perlite, 2-3% of sodium carbonate, 3-4% of calcium carbonate, 4-12% of sodium fluoride, and 4-15% of magnesium fluoride.

9. The method for preparing a high-strength conductive CuNiSi alloy according to claim 8, characterized in that: The preparation method of the second covering agent is as follows: acidified graphite, expanded perlite, sodium carbonate, calcium carbonate, sodium fluoride and magnesium fluoride are respectively put into an oven, the drying temperature is 100-200°C, the insulation time is 20-30 minutes, and then they are respectively crushed into particles with a particle size of 1-4 mm, and finally mixed according to the ratio of the second covering agent and stirred evenly.

Citation Information

Patent Citations

  • Covering agent for smelting scrap brass and its application

    CN104032155B

  • Copper alloy pipe fusion covering agent

    CN104593629A